Dilema Korban Dating Violence: Studi Kasus Persepsi Pribadi Perempuan - Andari, Putri; Savitri, Nita; Rifai, Muhammad (Aceh Anthropological Journal, 2025)
This study aims to explore the dilemma experienced by female victims of dating violence by examining the internal, external, and socio-cultural factors that prevent them from leaving abusive relationships. Employing a qualitative approach with ethnographic nuances, the research was conducted in Medan among late adolescent girls through observation and cultural theme analysis. The findings reveal that internal factors”such as the need for love, safety, esteem, and self-actualization (as proposed by Maslow), emotional dependency, fear of loss, and a lack of awareness of manipulative behaviors”significantly influence victims decisions to remain in harmful relationships. External factors, including the absence of a father figur, identity crises during adolescence, and the influence of social environments, further increase their vulnerability to emotional exploitation. In addition, socio-cultural factors also play a critical role in sustaining dating violence. Patriarchal norms, masculine dominance, and folklore surrounding female purity act as social controls that restrict women's autonomy and reinforce unequal gender relations. The intersection of these three dimensions”personal, social, and cultural”creates complex barriers that entrap victims in ongoing cycles of abuse, often without their full awareness. This study highlights the urgent need for comprehensive interventions, including relationship education, empowerment of adolescent girls, and the deconstruction of patriarchal values embedded in everyday life.Abstrak: Penelitian ini bertujuan untuk memahami dilema yang dialami perempuan korban dating violence (kekerasan dalam hubungan pacaran), dengan menelusuri faktor-faktor internal, eksternal, serta sosial budaya yang memengaruhi keputusan mereka untuk tetap bertahan dalam hubungan yang bersifat abusif. Menggunakan pendekatan kualitatif dengan nuansa etnografi, penelitian dilakukan di Kota Medan terhadap remaja perempuan akhir melalui observasi dan analisis tema kultural. Hasil penelitian menunjukkan bahwa faktor internal seperti kebutuhan dasar manusia (cinta, rasa aman, penghargaan), ketergantungan emosional, rasa takut kehilangan pasangan, serta ketidaksadaran akan kondisi manipulatif menjadi penghambat utama korban untuk keluar dari relasi yang merugikan. Sementara itu, faktor eksternal seperti kurangnya peran ayah, krisis identitas remaja, dan pengaruh lingkungan sosial memperkuat kerentanan korban terhadap eksploitasi emosional. Lebih lanjut, faktor sosial budaya juga berkontribusi signifikan terhadap normalisasi kekerasan dalam hubungan pacaran. Nilai-nilai patriarki, dominasi maskulinitas, serta keberadaan folklore tentang kesucian perempuan menjadi kontrol sosial yang mengekang dan menempatkan perempuan dalam posisi subordinat. Ketiga kategori faktor ini saling berkaitan dan membentuk kondisi yang membuat korban terus terjebak dalam siklus kekerasan tanpa menyadari bahwa hubungan tersebut telah merusak integritas diri mereka. Penelitian ini merekomendasikan pentingnya pendidikan relasi sehat, penguatan identitas diri, serta pembongkaran nilai-nilai patriarki dalam membangun sistem dukungan yang lebih adil dan transformatif bagi remaja perempuan.